2015
DOI: 10.1590/s0100-204x2015001000001
|View full text |Cite
|
Sign up to set email alerts
|

Calendário floral de plantas melíferas nativas da Borda Oeste do Pantanal no Estado do Mato Grosso do Sul

Abstract: Resumo -O objetivo deste trabalho foi avaliar o padrão de floração, ao longo do ano, de plantas melíferas na Borda Oeste do Pantanal, no Maciço do Urucum, MS, bem como o tipo de recurso oferecido pela flora melífera, para elaborar um calendário floral para a região. A floração das plantas melíferas visitadas pelas abelhas nativas e africanizadas foi acompanhada quinzenalmente, por 3 anos consecutivos, tendo-se anotado a data de florescimento, o hábito de crescimento e os recursos coletados pelos insetos. Foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…However, with a large number of extensive lakes and lagoons (Pantanal region of Nhecolândia and Paiagúas), water availability would not be a limiting factor (Gonçgalves et al, 2011;Mercante et al, 2011). Although high temperatures have been reported as limiting factors for the species (Le Conte & Navajas, 2008), the availability of food resources throughout the year contributes to the species' permanence in the area (Salis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, with a large number of extensive lakes and lagoons (Pantanal region of Nhecolândia and Paiagúas), water availability would not be a limiting factor (Gonçgalves et al, 2011;Mercante et al, 2011). Although high temperatures have been reported as limiting factors for the species (Le Conte & Navajas, 2008), the availability of food resources throughout the year contributes to the species' permanence in the area (Salis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…GS significantly reduced the severity of sulcus lesions, affecting dentin. No macroscopic abnormality or abnormality of the tissue was observed in the oral cavity of the animals throughout the experiment 16 Monteiro et al [28] The results of the chemical analysis showed that the samples were in accordance with the relevant regulations. The composition of vitamins and pollen types varied among the samples.…”
Section: N°bibliographic Referencementioning
confidence: 86%
“…In the multivariate analysis of the grouping, five groups were formed, due to the similarity of management, indicating the highest average production in hives in the most populous area of Santa Helena and lowest average production in the most populous of Marechal Cândido Rondon. The clustering of hives, differences in honey production, and floristic survey indicated that these differences could be associated with management and climatic differences recorded during the production period in the studied areas 06 Salis et al [16] The melliferous species evaluated in the region of the Urucum Massif, on the western border of the Pantanal, flourish throughout the year, with the highest number of species in summer (January to March) and lowest in winter (July to September). The interaction between the growth habit of melliferous plants and the climate influences the flowering season and causes herbs and lianas to flower mainly in summer and autumn (January to June) and trees and shrubs in the spring (late September to December).…”
Section: N°bibliographic Referencementioning
confidence: 93%
See 1 more Smart Citation
“…Sabe-se que a vegetação herbácea constitui a principal fonte de pólen e néctar para as Meliponini, principalmente no período das chuvas e na transição chuva-seca (Freitas, 1996;Marchini, 1999;Lopes et al, 2016). O estrato herbáceo também foi considerado o mais representativo em outros estudos envolvendo a flora melitófila (Locatelli et al, 2004;Santos et al, 2006;Pinheiro et al, 2008;Silva, 2014;Salis et al, 2015).…”
Section: Discussionunclassified